2017
DOI: 10.1021/acs.bioconjchem.7b00012
|View full text |Cite
|
Sign up to set email alerts
|

Preassembled Fluorescent Multivalent Probes for the Imaging of Anionic Membranes

Abstract: A new self-assembly process known as Synthavidin (Synthetic Avidin) technology was used to prepare targeted probes for near-infrared fluorescence imaging of anionic membranes and cell surfaces, a hallmark of many different types of disease. The probes were pre-assembled by threading a tetralactam macrocycle with six appended zinc-dipicolylamine (ZnDPA) targeting units onto a linear scaffold with one or two squaraine docking stations to produce hexavalent or dodecavalent fluorescent probes. A series of liposome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…The second major difference between POPC @CSP⊃6C and POPC @CSP⊃6Z liposomes was the fluorescence brightness. As shown in Figure B the fluorescence intensity of POPC @CSP⊃6Z liposomes was about four times lower, which matches previous observations that fluorescent ZnDPA complexes have a tendency to become self‐aggregated and self‐quenched on a membrane surface . As shown below, relief of this self‐quenching effect can be exploited to achieve target‐activated turn‐on fluorescence.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The second major difference between POPC @CSP⊃6C and POPC @CSP⊃6Z liposomes was the fluorescence brightness. As shown in Figure B the fluorescence intensity of POPC @CSP⊃6Z liposomes was about four times lower, which matches previous observations that fluorescent ZnDPA complexes have a tendency to become self‐aggregated and self‐quenched on a membrane surface . As shown below, relief of this self‐quenching effect can be exploited to achieve target‐activated turn‐on fluorescence.…”
Section: Resultssupporting
confidence: 88%
“…As shown in Figure A the threading of 6C was complete within a few seconds, whereas the threading of 6Z required ≈20 minutes (Figure A). Previous studies have shown that the threading of 6Z by a dispersed, water‐soluble squaraine is fast so the slow formation of POPC @CSP⊃6Z must be a liposome surface effect. The most likely explanation is surface promoted association of the ZnDPA units in the newly docked 6Z with neighbouring CSP conjugates, driven by Lewis acid/base interactions between the Zn II cations and the electron‐rich squaraine oxygen atoms, as reported for related metal cation/dye association systems .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, preliminary threading studies showedt hat near-quantitative threading occurred when H wasm ixed with one molar equivalent of R or C,o rH3H was mixed with two equivalents of R or C.I nF igure 1a,b are representative absorption spectra of the squaraine dyes before and after probe pre-assembly.T he absorption profile for free dimeric H3H is extremelyb road due to foldingo f the structure ands tacking of its two squaraine chromophores. [20,22] But after addition of macrocycle, near-quantitative threading and probe pre-assembly was indicated by the appearance of diagnostic narrow andr ed-shifted squaraine absorbance maxima. In Figure1c,d are two representative sets of absorption spectra showing the spectralc hanges that occur during the probe pre-assemblyp rocess.…”
Section: Resultsmentioning
confidence: 99%
“…Thisf inding is consistent with our previous work showingt hat Synthavidin pre-assembledp robesh ave sufficiently high kinetica nd thermodynamic stability to be effective biological imaging agents. [20][21][22] The cancert argeting capabilities of R'H and 2(R)'H3H were assessed using the integrin expressing cell lines OVCAR-4 and A549. OVCAR-4 is an excellent cell model of high-grade serous ovarian carcinoma because it has avery similar genomic sequence and response to chemotherapeutic drugs.…”
Section: Resultsmentioning
confidence: 99%